The Influence of Risk Mitigation on Firm Value with Profitability as an Intervening Variable - Novita Sari, Widya; Susanti, Neneng (Dinasti Publisher, 2026)
This study aims to analyze the effect of risk mitigation on firm value with profitability as an intervening variable in banking sub-sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. The independent variables in this research are Loan to Debt Ratio (LDR), Capital Adequacy Ratio (CAR), and Operating Expenses to Operating Income (BOPO). The dependent variable is Price to Book Value (PBV), while the intervening variable is Return on Assets (ROA). The study employs purposive sampling, multiple regression analysis, and Sobel test using SPSS 25 software, with a total sample of 45 banks listed on the IDX. The findings indicate a significant negative effect of LDR on ROA, a significant positive effect of CAR on ROA, and a significant negative effect of BOPO on ROA. Furthermore, LDR has a significant negative effect on PBV, CAR has a significant positive effect on PBV, BOPO has a significant negative effect on PBV, and ROA has a significant positive effect on PBV. ROA, as an intervening variable, is able to mediate the relationship between risk mitigation variables and firm value.